Factors on the Inclusion of Risk Disclosures Statement among Public Listed Companies in Malaysia - Nur Ameera Binti Shahazman, Siti; Hasniyanti Hassan, Hafinaz (International Journal of Psychosocial Rehabilitation, 2020)
This study emphasizes on the relationship between variables such as firm size, corporate governance, company’s leverage and company’s level of risk towards the inclusion of risk disclosures statement in annual reports among public listed companies in Malaysia. The variables data were extracted from the annual reports and SPSS software was used as the empirical tool for data analysis. The number of companies that had disclosed risk information in their annual reports was used as a proxy to measure the extent of risk disclosures provided by them. Time Series Analysis, Normality Test, Correlation Coefficient and Multiple Linear Regression Analysis, ANOVA and Coefficient of Determinants were used to test the influence of these four independent variables on the inclusion of risk disclosures in the companies’ annual reports. The proxies used for all the independent variables include number of independent directors’ company revenue for the year (firm size), number of independent directors within a company’s board (corporate governance), debt-to-equity ratio (leverage) and contribution margin (level of risk). Based on the findings, it can be concluded that a positive relationship exists between all of the independent variables and the inclusion of risk disclosures in the annual reports of the public listed companies in Malaysia.